Priorities and concerns of people who use opioids are key to scaling up XR-buprenorphine - Shover, Chelsea L. (Addiction, 2020)
Larence et al.’s findings have key implications for XR-buprenorphine guidelines as it becomes available internationally. These are to embrace less-onerous dosing schedules, to consider incorporating into standard-of-care an option to supplement with transmucosal buprenorphine between injections, and to investigate what possibilities XR-buprenorphine opens up for patients wanting to taper off opioid agonist treatment.